Valuation Of Eq-5d-5l Study For The Malaysian Population - Thakumar, Annushiah Vasan (2020)
With the rise of healthcare expenditure, prudent resource allocation decisions become vital and economic evaluations offer valuable information in guiding these decisions. Cost-utility analysis is one such alternative with outcomes measured using quality-adjusted life years (QALYs). QALYs takes into consideration health preference weights, with generic preference-based measures (PBMs) being most commonly used to generate these weights. One of the most widely used instrument todate, EQ-5D-5L has informed economic evaluation decisions throughout the world. However, Malaysia has yet to validate the measure and apply it to generate a countryspecific value set. Therefore, the main objective of this thesis is to estimate a valid EQ- 5D-5L value set for Malaysians. Two focus group discussions (FGDs) were held to explore the EQ-5D-5L dimensions understanding in Malaysians and investigate potential dimensions (bolt-ons) that may complement the concept of health. Next, using 100 conveniently sampled respondents, the influence of these identified bolt-ons on the current EQ-5D-5L dimensions were tested in a pilot setting in Penang. Subsequently, employing a cross-sectional multi-stage sampling design, an EQ-5D-5L nationwide valuation study was carried out by 18 trained interviewers on 1137 Malaysian general population. The psychometric properties of EQ-5D-5L were also assessed in the process. A variety of modelling methods were fitted onto the valuation data and performance of these models in predicting health state values were assessed using robust techniques.